Analysis of Current Status and Strategies of Retinopathy of Prematurity Screening during 6 Years in Local Regions of China: Implication and Caution - Lu Chen; Ming Su; Sheng-gang Ren; Hui-lan Hua; Jian-cang Wang; Wei Zheng (Journal of Ophthalmology)
Purpose. To understand the current status of retinopathy of prematurity (ROP) screening in a province of North China. Methods. We retrospectively analyzed 5651 cases with ROP screening in the Provincial Screening Center of Hebei Province from January 2008 to December 2013. Results. 14.98% of all ROP patients and 1.56% of severe ROP patients required treatment. All the severe ROP patients met the criteria of screening. Severe ROP patients were detected at recommended initial screening time (4–6 weeks after birth). The frequency of other ocular diseases was 8.03%, in which the main disease was fundus hemorrhage. In 2665 more mature and unqualified infants, only 2 retinoblastoma and 2 familial exudative vitreoretinopathy were detected, which indicates the advantage of early diagnosis and treatment based on fundus examination. Conclusions. It is suggested that the standard of GA < 32 weeks and/or BW < 1800 g could be served as the screening criteria in the local region for ROP screening. 4 weeks after birth is the most appropriate time for initial screening.